Study of Oil and Gas Well Drilling Process Scheme and Optimal Modeling System (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Drilling well design optimization reduces the overall cost allowance by reducing well construction time and costs. Well design is not a constant pattern throughout the life cycle of a mine. It should be optimized through continuous improvement for all aspects of well redesign based on actual field conditions and challenges. The main objective of this study is to provide an overview of well design optimization processes and to present existing research and applications for using well design optimization to solve well design problems so that economic efficiency and excellent well performance can be achieved. Well design optimization processes include unconventional design (thin holes) compared to casing construction, in addition to casing depth selection and casing string load optimization. Finally, we show the well trajectory design and optimization. The aforementioned optimization process significantly reduces drilling cost and time, as a fine hole design with a smaller casing and hole size reduces mud volume, steel costs and pump fuel costs. Optimum selection of casing seats can eliminate serious problems such as kicking and losses, which increase downtime without considering kicking tolerance and downhole pressure regime. Anticipating the optimal stress loads in the casing design is the most effective way to reduce the cost of casing strings, avoiding the additional cost of designing under unprofitable worst-case conditions. Optimizing the well trajectory with geomechanical considerations is important to reduce the problems associated with high torque, drag, formation collapse, resulting in pipe plugging and downtime.